Penguatan Self Awareness Guru Dalam Pembelajaran Melalui Pelaksanaan Supervisi - Besse Marhawati; Nina Lamatenggo; Darmawan Thalib; Sulkifly Sulkifly; Nurul Aini (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2026)
This community service program aims to enhance teachers’ understanding of self-awareness as a foundation for professional development, build collective awareness that academic supervision is a constructive form of professional guidance, equip teachers with reflective skills in teaching practices, and strengthen the role of principals as educational supervisors. The program was conducted at SDN 2 Tibawa, Tibawa District, Gorontalo Regency. The methods included socialization, mentoring, and collaborative academic supervision through both group and individual approaches. The results indicate that teachers’ understanding of the importance of self-awareness has improved, teachers increasingly perceive supervision as a constructive professional development process, and they have developed reflective abilities in planning, implementing, and evaluating learning. Additionally, the role of the principal as a supervisor has become more effective through collaboration with senior teachers in supporting continuous teacher competency development. Therefore, this program contributes to improving the quality of teaching and strengthening the academic supervision system in primary schools